Kinerja Tenaga Administrasi Sekolah (TAS) di SMK Negeri Kota Padang - Rahmi, Meilia; Nellitawati, Nellitawati (Lembaga Yasin AlSys, 2024)
This research is motivated by the results of observations of researchers to several State SMKs in Padang City which indicate the low performance of school administration personnel in State SMKs in Padang City. Therefore, the problem to be studied in this study is “how is the performance of School Administration Personnel (TAS) in State Vocational Schools in Padang City?”. Thus the purpose of this study is to obtain information and describe the performance of school administration personnel at SMK Negeri Kota Padang. The type of research used is descriptive with a quantitative approach. The population in this study were school administration personnel whose number was 153 TAS and the sample size was 63 TAS. The sample was drawn using the Slovin formula and taken using the Cluster Random Sampling technique. . The results of this study indicate that the performance of TAS in SMK Negeri Padang City is in the high category based on 4 indicators: 1) work quantity with an average score of 4.44, 2) work quality with an average score of 4.42, 3) punctuality with an average score of 4.40, 4) responsibility with an average score of 4.40. Overall, the performance of TAS in SMK Negeri Kota Padang is in the high category with an average score of 4.42.